IMPACT OF INFORMATION AND COMMUNICATION TECHNOLOGY IN ACADEMIC LIBRARIES - Sahu, Bhuleshwari; Mahilang, Dhankumar; Thakur, Avinash Singh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present paper clarifies the concept of information and communication technology. It will elaborate on the objectives of information and communication technology in libraries, benefits of information and communication technology for libraries, impact of information and communication technology on libraries and the role of librarians in the environment of information and communication technology. The main aim of this chapter is to make the readers understand the impacts of ICT on library environment, impacts of ICT on information formats, access and distribution, identify ICT as a tool which librarians should use to accomplish their goals.